Design of the New MST Radar in Chinese Meridian Project - Gang Chen; Zhiqiu He; Shaodong Zhang; Brian Fuller; Wanlin Gong; Guotao Yang; Weifan Zhang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2021)
With the support of the second phase of the Chinese Meridian Project, a new mesosphere-stratosphere-troposphere observation radar (MST radar), called Qinzhou MST radar, located in Qinzhou City, Guangxi Province, China (22°7'55''N,108°16'20''E) is under construction. The Qinzhou MST radar is a large VHF monostatic pulse Doppler radar with an active phased array antenna system, mainly using Doppler beam swinging technique for observation. The capability of multibeam observation, space antenna observation, and frequency- and spatial-domain interferometry are also employed. The main scientific objective of this radar is to explore the atmosphere dynamical processes at low latitudes of China. The observation of ionospheric field-aligned irregularities (FAIs) is also an important function of the radar. The radar applies a circular array composed of 1261 3-element crossed Yagi antennas with a diameter of 153 m and an aperture of near 2×104 m2. Thereinto, 997 elements connect both transmitting and receiving channels and 264 elements distributed near the edge connect only receiving channels. The peak power of the transmitter in each transmitting/receiving (T/R) module is 2 kW. The central frequency and bandwidth of the output signal are 50 and 4 MHz, respectively. The peak power of the whole system will be close to 2 MW. This article presents the initial design of the Qinzhou MST radar, and the construction will be completed at the end of 2022.